SIMULASI TINGKAT KEBISINGAN DAN KADAR POLUTAN SEBAGAI AKIBAT AKTIVITAS TRANSPORTASI PADA KAWASAN PERDAGANGAN DI KOTA KENDARI (Studi kasus: Kawasan Perdagangan Jalan MT. Haryono Kec. Wua-wua Kota Kendari) - Djalante, Susanti; Nurrakhmad, Laode Muh; Sugiyarto, Try (MEKTEK, 2013)
The rapid economic activity in Kendari is indicated by development of central business Lippo Plaza in MT.Haryono Roads Kendari. However, the consequences of the development of the central business LippoPlaza have affected on the environment in the form of increased noise and air pollution. The aim of thisstudy was to determine the level of noise and air pollution in the existing conditions, and to determine thelevel of noise simulation. The method used in this study for the noise calculations was based on